Legalitas Akta Perdamaian Non-Peradilan dalam Sengketa Harta Bersama dan Waris - Akbarudin Noor (Universitas Kapuas, 2026)
This research is intended to look into the legal aspects of certainty peace agreements (akta van dading) made outside the court in resolving disputes over marital property and inheritance. The research focuses on The judgment delivered by Tigaraksa’s Religious Court, Case No: 657/Pdt.G/2022/PA.Tgrs, as a concrete example of how the judiciary legitimizes informal agreements reached through deliberation between parties. The research uses a normative juridical approach, meaning it studies written laws and legal principles. involving An examination of the legal rules set by statute, legal doctrines, and court decisions. The findings reveal that although the peace agreement was made without the involvement Conducted by a qualified mediator, the court may still ratify the agreement as long as it meets the legal requirements of a valid contract and does not conflict with positive law. Judicial ratification provides legal legitimacy and executorial power to the agreement, while also strengthening the protection of vulnerable parties. These results highlight the importance of flexibility within the legal system to accommodate consensus-based dispute resolution, and reinforce. The judiciary functions as the protector of genuine fairness.